Risk Analysis and Occupational Health and Safety Assessment Series (OHSAS) at Hospital X Surabaya - Setiyaningrum, Dessi (Jurnal Kesehatan Masyarakat, 2024)
A hospital is a facility that generally raises the degree of public health. More and more human involvement makes hospitals have great potential to cause harm. To control the risk of accidents, it is necessary to identify hazards that exist in the workplace and evaluate the level of risk and control. One of the first stages in risk management is HIRARC (Hazard Identification Risk Assessment and Risk Control). The existence of HIRARC makes it easier to compile a risk register or hospital risk register in each work unit. This study aims to analyze the application of the Occupational Health and Safety Management System (OHSAS) at Hospital X Surabaya based on HIRARC. This type of research uses qualitative research with a research sample of 78 respondents. Qualitative variables in this research used for analyze risk management and identify risk control through the process of observation and interviews. Qualitative data analysis is carried out through identification of initial conditions, exposure of interview results and qualitative content analysis. The results of the study stated that the implementation of occupational safety and health management has been carried out at Hospital X Surabaya. OHS risk management is very important in preventing workplace accidents and improving performance. In this study, the HIRARC approach (Hazard Identification, Risk Assessment and Risk Control) found three levels of risk in hospitals, namely high risk, moderate risk and low risk. The results showed that the implementation of OHS risk management was used to identify, evaluate, and control OHS risk. The thing that cannot be avoided from work activities is a risk. Based on this, it is expected that there will be an increase in understanding and awareness related to OHS in hospitals, the application of risk control, routine evaluations and good cooperation and coordination between the OHS team and health workers for the implementation of OHSAS